Effect of surface topography and residual stress on the taper connection stability in total hip arthroplasty. (April 2022) - Mai, Phuong Thao; Bormann, Therese; Müller, Ulrike; Kretzer, Jan Philippe; Gibmeier, Jens
Abstract: In the present work, the influence of the trunnion surface topography and the near-surface residual stresses on the joining process of a taper connection is examined using a replicate of the realistic taper connection as it occurs in conventional hip joint implants. The focus of the work is on the surface of the taper trunnion made of Ti6Al4V ELI and its effect on the connection stability with a CoCrMo counterpart. In this regard, the interrelation between surface topography, residual stresses, the joining behavior and the corrosion behavior under dynamic loading have been systematically investigated. For this purpose, taper trunnions produced by means of three different machining processes were considered, i.e. fine machining, rough machining and a novel furrowing process. These mechanical surface treatments result in different surface topographies and near-surface work hardening and residual stress states. The results show that the primary taper stability is hardly altered by the different types of trunnion surfaces. For all three surface states, the joining/dismantling procedure did not change the residual stress state at the surface. After corrosion testing under dynamic loading, the fine machined taper surface exhibits the highest stability. Moreover, fine machined tapers consolidated during the dynamic corrosion experiment as the ratio between joining and dismantling force increased from 0.49 ± 0.04 to 0.83 ± 0.08. For the furrowed and rough machined taper surfaces, the connection stability showed a tendency towards increase and decrease, respectively, in the course of dynamic corrosion testing. The results indicate that for choosing an optimal taper trunnion surface, the effects of corrosion must be taken into account.